Tadpoles Inhabiting Natural and Anthropogenic Temporary Water Bodies: Which Are the Environmental Factors that Affect the Diversity of the Assemblages? - Camacho-Rozo, Claudia Patricia; Urbina-Cardona, Nicolás (Frontiers in Environmental Science, 2021)
The study of tadpole assemblages allows inferring habitat availability and using their occupation as a means of proxy for the effective reproduction of the species, contributing to complementary information for the study of their adult forms. In the Orinoco region, most amphibians have complex life cycles. These species deposit their eggs in lentic bodies of water, so it is important to know the effect of those environmental variables on larvae that inhabit natural ponds and anthropogenic puddles. Nine field surveys were taken from five temporary water bodies to determine the effect on anuran assemblages at the larval stage of aquatic habitats present in natural areas (savanna or gallery forest) or anthropogenic areas (road or pasture) and their interaction with water accumulation over time. Twenty environmental variables were evaluated and measured in the center of each water body. Of these, 14 variables characterized landscape elements and were measured only once during the study. The other six variables, representing physicochemical and structural characteristics of the water bodies, were measured weekly during the nine weeks of sampling. We explored differences in the structure and diversity of larval-stage anuran assemblages using statistical tests suitable for small sample sizes. Of the 14 species found, two species had very high abundances: Rhinella humboldti (19% of the total tadpole abundance); it is a generalist inhabiting the natural and anthropogenic water bodies, while Leptodactylus insularum (18% of the total tadpole abundance) was a specialist at natural pond in the savanna. The natural water bodies contained the highest number of species (between 10 and 12) and total abundance of larvae (between 847 and 485 individuals). In contrast, the anthropogenic water body tracks generated by tractors were only occupied by 2 species with 50 individuals in total, while the water body in anthropogenic pastures had 3 species with 474 individuals. The bodies of water immersed in natural cover were more diverse and had a greater degree of spatial and temporal species turnover. Our study emphasizes the importance of local processes, from environmental variables to human management activities, in the conservation of amphibian assemblages.